2019
DOI: 10.3389/fimmu.2019.03006
|View full text |Cite
|
Sign up to set email alerts
|

Combination of STING Pathway Agonist With Saponin Is an Effective Adjuvant in Immunosenescent Mice

Abstract: There is an urgent need to improve protective responses to influenza vaccination in the elderly population, which is at especially high risk for adverse outcomes from influenza infection. Currently available inactivated vaccines provide limited protection, even when a 4-fold higher dose of the vaccine is administered. Adjuvants are often added to vaccines to boost protective efficacy. Here we describe a novel combination of an activator of the STING pathway, 2 ′ ,3 ′ -cyclic guanosine monophosphate-adenosine m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
27
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(30 citation statements)
references
References 59 publications
1
27
2
Order By: Relevance
“…In comparison, 75% of aged mice immunized with Quil-A, a saponin adjuvant, with HA antigen immunization (i.d.) survived from influenza infection (33). Our observations here are in line with this latest result.…”
Section: Discussionsupporting
confidence: 93%
See 3 more Smart Citations
“…In comparison, 75% of aged mice immunized with Quil-A, a saponin adjuvant, with HA antigen immunization (i.d.) survived from influenza infection (33). Our observations here are in line with this latest result.…”
Section: Discussionsupporting
confidence: 93%
“…They immunized mice [subcutaneously (s.c.)] with 50 µg OVA antigen and 20 µg CDNs (32), a rather high dose of CDNs. In late December 2019, Vassilieva et al (33) showed that 2 ′ 3 ′ -cGAMP (5 (33). In comparison, 75% of aged mice immunized with Quil-A, a saponin adjuvant, with HA antigen immunization (i.d.)…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In late December 2019, Compans and R et al showed that cGAMP (5 µg) adjuvanted with 1 μg of hemagglutinin (HA) ( i.d. ) did not induce antibodies or protective immunity in the 19-month-old female BALB/c mice [ 94 ]. One hundred percent aged mice immunized ( i.d. )…”
Section: Confounding Factors In Cdn Adjuvanticity In Humansmentioning
confidence: 99%